PERANCANGAN DAN IMPLEMENTASI RESTFUL API PADA SISTEM INFORMASI MANAJEMEN DOSEN UNIVERSITAS UDAYANA - Kaniya Pradnya Paramitha, Ida Ayu; Wiharta, Dewa Made; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 9 No 3 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i03.p3, 2022)
Lecturer Management Information System (SIM Dosen) Udayana University is a management information system to assist lecturers in improving performance in providing higher quality education. SIM Dosen was designed using a monolithic architecture will switch to a microservice architecture that is more flexible because it breaks down several applications into several services. Communication between services is carried out through the HTTP protocol using a RESTful API. This research focuses on the success of designing a RESTful API on one of the modules on the SIM Dosen which is “data dosen” module. RESTful API was successfully designed using the Java programming language and MySQL database. Testing the RESTful API functionality using the black box testing method and Postman on local device for GET, PUT, and DELETE method display a 200 response code and OK status, and for POST method display a 201 response code and Created status which indicate all the functions of each HTTP method used in “data dosen” module have been running according to their functions.